PEMBERIAN SARI BENGKUANG TERHADAP KADAR GLUKOSA DARAH PUASA PADA PENDERITA DIABETES MELLITUS TIPE 2 - Yunita Dwi Nunggaryati; Ria Ambarwati; Sri Noor Mintarsih; Sunarto Sunarto; Yuwono Setiadi (JURNAL RISET GIZI, 2019)
Background : Diabetes mellitus is a condition in which blood levels in the body is high due to a disruption in the pancreas gland so the body can not produce or can not use insulin. Diabetes mellitus type 2 is a type of diabetes mellitus that does not depend on insulin or better known as non-insulin-dependent. Prevalence of Diabetes Mellitus in Central Java was ranked 2nd out of 8 new cases of PTM (Non Communicable Disease), with a percentage of 18.44%. Control efforts can be done by eating high-fiber foods, one of the foods that contain fiber is high enough and potentially lower blood glucose levels, namely bengkuang. Objective: To determine the effect of bengkuang juice on fasting blood glucose level in type 2 diabetes mellitus. Research Methods : Type of quasy experiment study with pretest-posttest control group design. The population is patients of type 2 diabetes mellitus aged 40-60 years in the work area of Kedungmundu Public Health Center in April as many as 60 people. Sampling using non randomized sampling technique. The sample size is 36 people divided into 18 treatment groups and 18 control groups. Intervention given in the form ofbengkuang juice for 14 days. Multivariate test using anova repeated measured.Results : The giving of bengkuang juice controlled by nutrient intake (energy, protein, fat, carbohydrate and fiber) showed no significant effect on decreasing fasting blood glucose level (p = 0.344). Conclusion: Bengkuang juice has no significant effect on decreasing fasting blood glucose level in type 2 diabetes mellitus.